The Correlation of Gross Motor Skills and the Quality of Life in Children with Cerebral Palsy - Nahdiah Purnamasari; Wardatun Wahdaniyah Rasidi; Nurhikmawaty Hasbiah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The quality of life in children with cerebral palsy is very important to be studied along with the factors that influence it to improve the quality of health services. The Problem of quality of life in children with cerebral palsy is not only influenced by socio-economic aspect, but also health aspect, such as physical health, pain and motor limitation which is experienced by children. This study aims to determine the relationship between gross motor skills and the quality of life of children with cerebral palsy in Makassar. This study used a cross-sectional design with thirty people as the sample (n = 30). They are students who got cerebral palsy at SLB YPAC Makassar, SLB Negeri 1 Pembina at South Sulawesi Province, SLB Laniang and SLB Reskiani Makassar. There are several primary data collected including gross motor skills and quality of life. The data were collected using the PedsQLTM 3.0 questionnaire for the cerebral palsy module and the GMFCS-E & R (Gross Motor Function Classification System Expanded and Resived) measurement guide. Based on the results of the analysis of the relationship test with the fisher exact test, it was found a significance value (p) of 0,037 (p <0.05) with a relative risk value for poor and very bad quality of life, namely 0.714, which means that there is a relationship between gross motor skills and quality of life, with children cerebral palsy who have mild and moderate gross motor skills have a chance to have very poor and poor quality of life 0.714 times less than cerebral palsu children who have severe gross motor skills (N = 30).